2004
DOI: 10.1074/jbc.m402337200
|View full text |Cite
|
Sign up to set email alerts
|

A Frameshift Mutation and Alternate Splicing in Human Brain Generate a Functional Form of the Pseudogene Cytochrome P4502D7 That Demethylates Codeine to Morphine

Abstract: A frameshift mutation 138delT generates an open reading frame in the pseudogene, cytochrome P4502D7 (CYP2D7), and an alternate spliced functional transcript of CYP2D7 containing partial inclusion of intron 6 was identified in human brain but not in liver or kidney from the same individual. mRNA and protein of the brain variant CYP2D7 were detected in 6 of 12 human autopsy brains. Genotyping revealed the presence of the frameshift mutation 138delT only in those human subjects who expressed the brain variant CYP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 36 publications
0
65
2
Order By: Relevance
“…Recently, a functional variant of CYP2D7 leading to expression of this pseudogene in brain and to brain metabolism of codeine to morphine has been described in four of eight individuals of whom brain autopsies were obtained. 37 The population frequency of this variant has not yet been studied so far but this mechanism as well might be a possible explanation for opioid effects in PMs after codeine intake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a functional variant of CYP2D7 leading to expression of this pseudogene in brain and to brain metabolism of codeine to morphine has been described in four of eight individuals of whom brain autopsies were obtained. 37 The population frequency of this variant has not yet been studied so far but this mechanism as well might be a possible explanation for opioid effects in PMs after codeine intake.…”
Section: Discussionmentioning
confidence: 99%
“…The obtained PCR product was used as a template for the single-base primer extension reaction (SNaPshot, Applied Biosystems) designed to genotype the polymorphic position 4180G4C of the upstream gene-copy and positions À1584G4C and 100C4T of the downstream gene-copy. The following primers were used for the extension reactions: À1584G4C, 5 0 -(A) 9 CCT GGA CAA CTT GG AAG AAC C-3 0 ; 100C4T, 5 0 -(A) 31 CAA CGC TGG GCT GCA CGC TAC-3 0 and 4180G4C, 5 0 -(A) 37 CAA AGC TCA TAG GGG GAT GGG-3 0 . The single-base primer extension reactions were performed according to the manufacturer's instructions (SNaPshot, Applied Biosystems, Weiterstadt, Germany).…”
Section: Genotypingmentioning
confidence: 99%
“…13,14 The question arises whether such an activity is essential. Interestingly, Pai et al 15 have recently provided evidence that a common variant of the pseudogene CYP2D7P could be expressed in an active …”
Section: General Characteristics Of Cyp2d6mentioning
confidence: 99%
“…It has been observed that sometimes a frame-shifted protein coding gene is still functional [2,14,15,26], but this phenomenon has been taken as special or individual cases, rather than a fundamentally important biological process sharing a common underlying mechanism. In fact, we found that this phenomenon is not rare, but can be observed quite often.…”
Section: / 22mentioning
confidence: 99%
“…Therefore, although it was observed that sometimes frame shifted or overlapped genes is functional [12][13][14][15][16][17], a frame-shifted translational product is generally considered to be non-functional, because it is a common sense that it is often possible to inactivate the function of a peptide by changing only one single residue.…”
Section: Introductionmentioning
confidence: 99%